THE EFFECT OF PRODUCT QUALITY AND SERVICE QUALITY ON PURCHASE DECISION AT MIE GACOAN - Lalu Supardin; You She Melly Anne Dharasta; Awan (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
This study aims to examine the effect of product quality and service quality on purchase decision at Mie Gacoan. The type of research used in this research is quantitative research. The sampling technique used was purposive sampling. The population in this study are consumers in Yogyakarta. The sample in this study were 130 respondents. The data used in this study is primary data sourced from the data collection process using a questionnaire. This study uses multiple linear regression analysis technique with SPSS as an analytical tool. Based on the results of data testing, it shows that: (1) Product quality partially has a significant effect on purchase decision at Mie Gacoan in Yogyakarta. (2) Service quality partially has a significant effect on purchase decision at Mie Gacoan in Yogyakarta. (3) Product quality and service quality simultaneously have a significant effect on purchase decision at Mie Gacoan in Yogyakarta.